Penerapan STEM FROM HOME dengan Model PjBL untuk Meningkatkan Penguasaan Konsep dan Keterampilan Berpikir Kreatif Siswa SMP - Resmi Ningrum; Taufik Rahman; Riandi Riandi (University of Bengkulu, 2022)
Learning from home is less effective, so teachers are required to be able to plan learning activities that are simpler, creative and effective. Project Based Learning (PjBL) is one of the learning models that recommended by the government. In order to combine contextual with project assignments, achieving 21st century skills is carried out through the implementation of the PjBL model with a STEM (Science, Technology, Engineering and Math) approach that is carried out at home. This study aimed to obtain information on the application of STEM from home with the PjBL model to mastery of concepts and creative thinking skills. This study used an experimental method without using a control group (Pre-Experimental) with a